OPTIMIZING A PRODUCTION LINE OF A PRINTING HOUSE IN MEXICO - Arriaga-Martinez, Antonio Alejandro; Gamba-Lavin, Ricardo (European Scientific Journal, ESJ, 2014)
In this paper, is described the use of simulation to determine the real production capacity of Centro Gráfico Industrial which is an important printing house at Mexico City. First it was necessary to obtain data from the company. Once this information was obtained five scenarios were developed as potential responses to improve. Based on the simulation results, a series of recommendations were made in order to maximize production rates and minimize time consumption for each process, and therefore optimize results on the bottom line in terms of average hours per order. This process can also be applied to similar situations in companies throughout the world to improve their competitiveness in increasingly demanding markets.